PERAN GURU DALAM PENERAPAN DISIPLIN SISWA SMA - Meyanti, Riska (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis thesis entitled â€œThe Roles of Teacher in Discipline Implementation on the Eleventh Grade Students of SMAN 4 Sungai Rayaâ€. The main problem in this research is what is the teacherâ€™s roles in discipline implementation the eleventh grade student. This reasearch applied a descriptive qualitative method. The research technique used was observation, interview, and documentation. The research result show that the role of teacher in the application of discipline. First, the discipline of time that the teacher has given an example to the students by coming to the school and getting to the classroom on time when the lesson. Second, discipline to enforce the rules is the teachers has enforced the existed rulesin the school by giving a sanction to the students who breaks the school rules. Third, attitude discipline is the attitude taken by the teacher is well seen from the treatment of teachers to the students when the students make a mistake. The penalties covered cleaning toliets and floor, parking, carrying water, put the rubish into the bin, and watering the plants. This discipline implementation were given to the students in both indoor and outdor learning process.Â Keywords: Teacherâ€™s Role, Discipline Implementation, StudentÂ